A detailed analysis of surgical site Infections and risk factors: A multicentric cohort study in Türkiye - Aktas, Aydin; Güner, Ali; Güneş, Örgün; Karagül, Servet; Karaköse, Oktay; Çolak, Elif; Kayaalp, Cuneyt (Ondokuz Mayıs Üniversitesi, 2024)
There is limited data on surgical site infection (SSI) in developing countries. The aim of this study was to investigate the incidence and risk factors of SSI following general surgical operations in Türkiye. This multicenter cohort study was conducted at 10 centers. Patients who underwent thyroid/parathyroid, breast, hernia and abdominal surgery between September 2017 and March 2018 were included in the study. Center for Disease Control and Prevention 2016 (CDC-2016) criteria was used for the diagnosis of SSI. Patients were followed for 30 days (90 days for mesh patients). Out of 1871 patients included, SSI occurred in 181 (9.7%) patients. Of these SSI, 101 (55.8%) were superficial, 41 (22.7%) deep, and 39 (21.5%) organ/space SSI. SSI incidence was seen to be high (>15.0%) following some surgeries (40.0% in pancreas, 39.1% in biliary duct, 30.3% in small bowel, 27.9% in colorectal, 27.3% in esophagus, 24.1% in liver, 15.7% in gastric). SSI incidences were generally ?5.0% after some surgeries (4.4% in hernia, 4.2% in gallbladder, 3.3% in morbid obesity, 1.4% in breast, 0.8% in thyroid/parathyroid, and zero in spleen and surrenal). In univariate analysis, age ?60 years, female sex, preoperative weight loss, presence of comorbidities, preoperative albumin ?3.5 g/dL and hemoglobin ?12 g/dL, wound classification, ASA score, general anesthesia, emergency surgery, open surgery, operation time ?4 hours, intraoperative blood loss ?400 ml, perioperative blood transfusion, drain placement, distant infection and malignant disease were associated with SSI. In multivariate analysis preoperative weight loss, clean-contaminated wound, general anesthesia, emergency surgery, open surgical technique, prolonged operation duration (?4 hours), drain placement, and distant infection were found to be independent variable for SSI risk. In order to reduce the incidence of SSI, patients with a weight loss of 10% or more in six months preoperatively should be identified, and nutritional status of the patients should be corrected preoperatively, laparoscopic technique should be preferred in abdominal surgeries, and drain placement should be avoided, especially in clean-contaminated wounds.
Keywords: General Surgery; Genel Cerrahi